Analysis of Arabic Learning Evaluation Using Blanded Learning Method at Senior High School of Al-Izzah Batu/ Analisa Evaluasi Pembelajaran Bahasa Arab dengan Menggunakan Model blanded Learning di SMA Al-Izzah Batu - Maftuhin Maftuhin; Junaedi (Journal of Arabic Language Studies and Teaching, 2021)
This article explains how important evaluation is one of the components of education, especially in Arabic language education activities. In an education process, there are two fundamentals activities, they are learning and studying by the students and teaching by the teachers, these activities are needed to achieve the goals made in learning planning. This research’s purpose is to give an illustration about the implementation of blended learning especially when virtual learning is conducted. This research also uses qualitative measure about the method of case studying, in which the data are collected through interviews, observations and the study of documents. Based on the result of the research, the teachers prepare RPP, syllabus, face-to-face scheduling, learning resources and evaluation method in a form of a soft file during the planning process. The education process is performed by three steps which are first, main and last activity. The evaluations on the education are assignments giveaway, mid and final examinations. Unfortunately, during its implementation, teachers face some obstacles in it.